Influence of Bacillus spp. strains on seedling growth and physiological parameters of sorghum under moisture stress conditions. (11th September 2013) - Grover, Minakshi; Madhubala, R.; Ali, Sk. Z.; Yadav, S. K.; Venkateswarlu, B.
<x xml:space="preserve">Abstract</x> Microorganisms isolated from stressed ecosystem may prove as ideal candidates for development of bio‐inoculants for stressed agricultural production systems. In the present study, moisture stress tolerant rhizobacteria were isolated from the rhizosphere of sorghum, pigeonpea, and cowpea grown under semiarid conditions in India. Four isolates KB122, KB129, KB133, and KB142 from sorghum rhizosphere exhibited plant growth promoting traits and tolerance to salinity, high temperature, and moisture stress. These isolates were identified as Bacillus spp. by 16S rDNA sequence analysis. The strains were evaluated for growth promotion of sorghum seedlings under two different moisture stress conditions (set‐I, continuous 50% soil water holding capacity (WHC) throughout the experiment and set‐II, 75% soil WHC for 27 days followed by no irrigation for 5 days) under greenhouse conditions. Plate count and scanning electron microscope studies indicated successful root surface colonization by inoculated bacteria. Plants inoculated with Bacillus spp. strains showed better growth in terms of shoot length and root biomass with dark greenish leaves due to high chlorophyll content while un‐inoculated plants showed rolling of the leaves, stunted appearance, and wilting under both stress conditions. Inoculation also improved leaf relative water content and soil moisture content. However, variation in proline and sugar content in the different treatments under two stress conditions indicated differential effect of microbial treatments on plant physiological parameters under stress conditions.